The Economic and Environmental Sustainability of Dual Sourcing - Heidrun Rosic (Peter Lang International Academic Publishers, 2012)
Supply chains consist of all processes which are needed in order to supply customers with the required products. Traditionally, supply chain management decisions are based on the economic performance of the involved parties. But in recent years, other criteria, such as quality, flexibility or the environment, have become important as well. Especially carbon emissions are high on the political agenda because they are considered to be a major cause of the greenhouse gas effect. In this work it is shown how the performance of supply chains can be evaluated considering both economic and environmental criteria. In particular, the work deals with dual sourcing in the context of the newsvendor model. The impact of environmental regulations (emission taxes and emission trading) on the decisions of companies is analysed.
Keywords: 330